A Study of the Understanding amongst Academia towards the Islamic Concept of Breastfeeding - Normadiah, Daud; Azimah Shurfa, Mohammed Shukry; Nadhirah, Nordin (Canadian Center of Science and Education, 2014)
Understanding the importance of breastfeeding from the Islamic perspective is important in ensuring the success of breastfeeding particularly amongst working mothers. The focus of this research is the understanding of the Islamic perspective on breastfeeding amongst university intellectuals who are considered to be highly educated and a role model for other women. This is a field study that employed the quantitative method where data were obtained through questionnaires and an interview with a specialist in the Islamic Family Jurisprudence (Fiqh). A total of 140 respondents were selected from the Malaysian higher education institutes such as UiTM Kuala Terengganu, University Malaysia Terengganu and Universiti Sultan Zainal Abidin, Kuala Terengganu. The results showed that the respondents have a sound understanding with regards to breastfeeding from the Islamic perspective, scoring an average mean value of 2.67-3.92. This finding indicates that knowledge about breastfeeding according to Islam is an important foundation to the successful practice of breastfeeding.